2021
DOI: 10.1039/d1cp01704g
|View full text |Cite
|
Sign up to set email alerts
|

Molecular properties affecting the hydration of acid–base clusters

Abstract: In the atmosphere, water in all phases is ubiquitous and plays important roles in catalyzing atmospheric chemical reactions, participating in cluster formation and affecting the composition of aerosol particles. Direct...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…In particular, particle formation by nucleation is still not well understood and is difficult to represent in models (Kerminen et al, 2018). One of the dominant nucleation pathways is through salt formation, where the formation of a cluster is stabilized by the interactions between acid and base molecules, which enhances particle formation (Ball et al, 1999;Kirkby et al, 2011;Kürten et al, 2016;Nadykto and Yu, 2007;Nadykto et al, 2015;Wang et al, 2018). This nucleation pathway is particularly dominant in urban environments, where anthropogenic sources for acidic and basic gases are abundant (Ge et al, 2011;Kirkby et al, 2011;Qiu and Zhang, 2013;Weber et al, 1996;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, particle formation by nucleation is still not well understood and is difficult to represent in models (Kerminen et al, 2018). One of the dominant nucleation pathways is through salt formation, where the formation of a cluster is stabilized by the interactions between acid and base molecules, which enhances particle formation (Ball et al, 1999;Kirkby et al, 2011;Kürten et al, 2016;Nadykto and Yu, 2007;Nadykto et al, 2015;Wang et al, 2018). This nucleation pathway is particularly dominant in urban environments, where anthropogenic sources for acidic and basic gases are abundant (Ge et al, 2011;Kirkby et al, 2011;Qiu and Zhang, 2013;Weber et al, 1996;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, compared to carboxylic acids without hydroxyl groups, clusters with more hydroxyl groups are likely more hydrophilic as more hydrogen bond donors and could further interact with other molecules to contribute to growth on both sides according to a previous study showing that water uptake by ammonium bisulfate clusters depends on the total number of free hydrogen bond donors in clusters 102 as well as for sulfuric acid–dimethylamine clusters. 103…”
Section: Resultsmentioning
confidence: 99%
“…33 Moreover, we speculate that the added hydroxyl group can increase the hydrophilicity of the system as a hydrogen bond donor, while the carbonyl group is opposite. 103 TA may present higher enhancement to NPF involving SA and DMA than MA, which requires more experiments to verify.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was demonstrated by our recent work where we found that formic acid is as effective as ammonia for the formation of clusters with sulfuric acid and water . Including water molecules results in the formation of hydrogen-bond networks. , Sulfuric acid can form comparably stable clusters with atmospheric species other than bases, such as formic acid , and amino acids. In these cases, the ability of functional groups to form strong intermolecular interactions is key to the thermodynamic stability of the cluster. , Amino acids are enriched in sea spray aerosols by up to 7 orders of magnitude, and they are driven to the aerosol air–water interface in salts and acidic environments . At the interface, they are more reactive, including for the formation of peptide bonds. Yet, amino acids without the presence of sulfuric acid do not drive aerosol formation .…”
Section: Introductionmentioning
confidence: 93%